High-temporal resolution optical observations of the gamma-ray blazar PG 1553+113 - Andruchow, Ileana (2011)
We present here the results of an observational photo-polarimetry campaign at optical wavelengths of the blazar PG 1553+113, which was recently detected at very high energies (>100 GeV) by the H.E.S.S and MAGIC ã-ray experiments. Our high-temporal resolution data show significant variations in the linear polarization percentage and position angle at inter-night time-scales, while at shorter (intra-night) time-scales both parameters varied less significantly, if at all. Simultaneous differential photometry (at the B and R bands) shows no significant variability in the total optical flux.